Penggunaan Media Sosial Pada Proses Pembelajaran Online Menggunakan Analisis Diskriptif Kuantatif - Winarti (FT- UNDAR, 2021)
The development of knowledge in the field of information and communication technology has received positive support from the world of education. The development of computers and supporting software can help in the visualization of objects or abstract concepts. The online learning system is one of the information technology breakthroughs that offers flexibility in a learning system. In addition, online media is very effective in creating an open learning environment, therefore online learning media is needed. One of the media is Facebook and Telegram. The purpose of this development is to utilize Facebook and Telegram as a means of collaboration in the world of learning. In addition, it is also to determine the effectiveness of the interactions that occur in online learning. Facebook and telegram learning was developed as material for social media groups by utilizing websites, blogs, yahoogroups, virtual laboratories, and google as supporting programs. The advantage of Facebook is that it is equipped with chat facilities that provide other sites. Facebook is a place for teachers, students, and enthusiasts of thermochemistry to interact outside of the classroom. Facebook was developed to be used for learning group members without the presence of a teacher or instructor, can be accessed by group members at any time and costs are relatively affordable, and can support information technology-based network programs according to government programs